Nespolo, l’acculturazione - Tommaso Trini (Rivista di Estetica, 2015)
The poetic of Nespolo’s first artistic period of production is characterized by an intensive conceptualist approach based on activism, social contestation and on the use of objects and materials. These are artistic activities characterised by a critical reflection on action and on the use and consequences of art.